Novel mutations in CYP4V2 in Bietti corneoretinal crystalline dystrophy: Next-generation sequencing technology and genotype-phenotype correlations - Meng, Xiao Hong (Mol Vis, 2019)
PURPOSE: To identify any novel mutations in CYP4V2 in 85 Chinese families with Bietti corneoretinal crystalline dystrophy (BCD) by using next-generation sequencing, and to summarize the mutation spectrum in this population, along with any genotype-phenotype correlations. METHODS: A total of 90 patients with BCD from 85 unrelated Chinese families were recruited. All probands were analyzed by using gene chip-based next-generation sequencing, to capture and sequence all the exons of 57 known hereditary retinal degeneration-associated genes. The candidate variants were validated with PCR and Sanger sequencing. RESULTS: Twenty-eight mutations were detected in all patients, including thirteen novel mutations (five missense, six deletions, one splicing and one frame-shift mutations) and 15 previously reported mutations. Mutations in 64 patients were inherited from their parents, while three patients had de novo mutations. c.802–8_810del17insGC was the most common mutation, accounting for 78% of the mutations. Although 16 patients were homozygous at this site, the clinical features of all 16 patients were highly heterogeneous. CONCLUSIONS: These results expand the spectrum of mutations in CYP4V2, and suggest that mutations in CYP4V2 may be common in the Chinese population. The phenotype of patients with the homozygous mutation (hom.c.802–8_810del17insGC) is highly heterogeneous.